The View of Changing the Testimony of istihsan At the Level of Debates Between Ahli Hadith and Ahli Rai - Vakilov, Ramin (Scholarya Demo Journal of Ruby, 2022)
Ahl-i hadith and Ahl-i-rai are the two most rooted traditions of Islamic thought. The rivalry between them has an important place in the historical development of Islamic law. The hottest topic of discussion between these two systems is the question of the role of reason in obtaining the provisions of sharia. Discussions and debates on the proofs of istihsan, an intellectual fiqh method, are important in examining the historical development of Islamic law. The issue of istihsan brought by Hanafis to fiqh is not an ordinary argument in fiqh but rather a way of approaching law as an alternative to "qiyas" evidence, which has become a philosophy of law or the practice of dogmas frozen in time. The proof of istihsan, which includes a rational method and focuses on the purpose and goal of the law, has been subjected to serious criticism from the scholars of Ahl-i Hadith since the first days of the formation of fiqh as a science. These criticisms, which were put forward most systematically by Muhammad ibn Idris al-Shafii, the great thinker of Ahl alHadith thought, were affected. Starting from the middle of the 4th century AH, Hanafis revised the istihsan method and interpreted it as proof of comparison. The proofs of istihsan introduced as an alternative to qiyas became almost the same as qiyas in a few centuries later. These comments of the Hanafis left an impression on the opposition Ahl-i Hadith front. In the tradition of Ahl al-Hadith, criticism has become more moderate, and Hanafis have tried to understand the method of istihsan. Even the Hanbalis, among the most original followers of the Ahl-i Hadith thought, have taken istahsan as evidence in their methodology. However, the narrative of the Ahl-i Hadith on logic, which they accepted as istihsan, was nothing more than a relative choice of evidence.